Menelusuri Sosok Kartini Melalui Liniearitas Alur Naratif Propp Dalam Novel Biografi Karya Pram - Regina Caeli Cahaya Tarsisty; Rustono Farady Marta; Joshua Fernando (Jurnal Komunikasi, 2021)
Abstract. Gender discrimination in Indonesia has existed since ancient times. As a Javanese woman, Kartini became a figure who experienced the past and even by her family. Due to her limitations, Kartini wrote about her restlessness and thoughts in the form of letters sent to her Dutch friends. The letters were then collected and put together into a book entitled Door Duisternis tot Licht. Pramoedya took some fragments of Kartini's letter, and tried to see Kartini in her literary glasses in the biographical novel Call Me Kartini Saja. Relying on qualitative methods and constructivist paradigms and using Vladimir Propp's narrative analysis, the purpose of this research is to reveal the description of the character's function in the narrative in the novel. The role analysis is only in narratives that contain elements of feminism. This research found that the novel P Call Me Kartini Saja contains seven of the 31 narrative functions and seven characters which are grouped into four character functions. Through the narrative function and character function that have been analyzed in this novel, this suggestion suggests that Kartini's spirit in fighting for emancipation through her writing and thoughts should always be lived out in her daily activities because her struggle allowed Indonesian women to indulge their rights.Keywords: Liniearity, Kartini, Woman Emancipation, Gender Roles,Vladimir Propp’s Narrative Analysis.